Fabrication of thermoelectric modules and heat transfer analysis on internal plate fin structures of a thermoelectric generator. (15th September 2016) - Kim, Tae Young; Lee, Seokhwan; Lee, Janghee
Highlights: Customized thermoelectric modules are fabricated for waste heat recovery. A thermal resistance model is developed to simplify numerical simulations. A plate fin structure is numerically optimized to improve conversion efficiency. The numerical results are validated using experimental results and a correlation. An equation is proposed to predict thermal resistances of fins in heat absorption. Abstract: Thermoelectric modules (TEMs) are fabricated for a low-temperature waste heat recovery application. Each module has a surface area of 44 × 44 mm and a thickness of 3.6 mm, including a 1-mm-thick ceramic substrate on each side. Prior to fabrication of the system, a series of numerical simulations are conducted to optimize the design of the internal finned structures of a thermoelectric generator. To reduce the difficulty of designing the numerical models, a thermal resistance model is employed to determine the thermal conductivity of the TEM. The optimal number and thickness of the fin structures are determined with respect to the maximum allowable module temperature and the pressure drop characteristics. The accuracy of the numerical model is validated using an existing friction factor correlation and experimental results. The numerical results show that having six 2-mm-thick plate fins on the hot surface of each TEM would provide the most effective temperature fields for TE power generation while keeping the surface temperature of the TEM from exceeding the allowable maximum of ∼473 K. The pressure drop across the fins is found to increase with increasing number and thickness of fins. However, the module-level pressure drop is in the range of several pascals, which has a negligible effect on the combustion characteristics of the engine. A thermal resistance equation is proposed to predict the heat transfer characteristics of plate fins employed for thermoelectric generators for heat absorption.